THE PRIORITY NEEDS FOR DEVELOPING STUDENT AFFAIRS MANAGEMENT OF SUANKULARB WITTAYALAI AFFILIATED SCHOOLS IN BANGKOK METROPOLITAN REGION BASED ON THE CONCEPT OF RESILIENCE - Chanpanya , Warissara; Xupravati, Penvara (Journal of Educational Review Faculty of Education in MCU, 2024)
The purpose of this research is to study the priority needs in the Student Affairs Management Development of Suankularb Wittalai Affiliated in Bangkok Metropolitan Region, based on the Concept of Resilience. A descriptive research method was used in this research. The tool used in the research was questionnaires and the data was analyzed by Arithmetic mean, Standard Deviation and the Modified Priority Needs Index (PNIModified). The survey was completed by 108 people, including school administrators and secondary school teachers at Suankularb Wittalai Affiliated in Bangkok Metropolitan Region.The finding showed that. The Priority Need Index, the overall student affairs management concept was 0.388 (PNIModified = 0.388). In consideration of the scope of student affairs management, it illustrated student that activities or extra-curricular activities present the highest order of needs, where as the student care dimension present the lowest order of needs. To consider the attributes of Resilience, it was 0.390 (PNIModified = 0.390). That encouraging students to have self-control had the highest of development needs while promoting a sense of purpose in life for students had the lowest of development needs.